2009
DOI: 10.2337/db09-0323
|View full text |Cite
|
Sign up to set email alerts
|

The C3a Anaphylatoxin Receptor Is a Key Mediator of Insulin Resistance and Functions by Modulating Adipose Tissue Macrophage Infiltration and Activation

Abstract: OBJECTIVESignificant new data suggest that metabolic disorders such as diabetes, obesity, and atherosclerosis all posses an important inflammatory component. Infiltrating macrophages contribute to both tissue-specific and systemic inflammation, which promotes insulin resistance. The complement cascade is involved in the inflammatory cascade initiated by the innate and adaptive immune response. A mouse genomic F2 cross biology was performed and identified several causal genes linked to type 2 diabetes, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
174
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(185 citation statements)
references
References 48 publications
8
174
2
1
Order By: Relevance
“…The anaphylatoxins C3a and C5a, by acting on their respective receptors (48-50), attract and activate leukocytes and increase the synthesis of proinflammatory cytokines Table 3-Analyses of changes in plasma C3 levels with changes IR and glucose tolerance over a 7-year period (n = 394 at baseline and follow-up) by several cell types, including leukocytes and Kupffer cells (8)(9)(10)(11)(12)50,51). Indeed, blocking of anaphylatoxic pathways in C3aR-or C5aR-knockout mice fed a high-fat diet led to decreased adipocyte size, less liver steatosis, less adipose tissue infiltration by macrophages, a reduction in tissue and plasma proinflammatory cytokines, and less systemic IR (48,51), and inhibition of C3a and C5a signaling by blocking their receptors appeared to induce similar effects (50). As such, complement activation and the subsequent local and/or systemic inflammation may actively contribute to the development of IR and T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…The anaphylatoxins C3a and C5a, by acting on their respective receptors (48-50), attract and activate leukocytes and increase the synthesis of proinflammatory cytokines Table 3-Analyses of changes in plasma C3 levels with changes IR and glucose tolerance over a 7-year period (n = 394 at baseline and follow-up) by several cell types, including leukocytes and Kupffer cells (8)(9)(10)(11)(12)50,51). Indeed, blocking of anaphylatoxic pathways in C3aR-or C5aR-knockout mice fed a high-fat diet led to decreased adipocyte size, less liver steatosis, less adipose tissue infiltration by macrophages, a reduction in tissue and plasma proinflammatory cytokines, and less systemic IR (48,51), and inhibition of C3a and C5a signaling by blocking their receptors appeared to induce similar effects (50). As such, complement activation and the subsequent local and/or systemic inflammation may actively contribute to the development of IR and T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated by significant changes in adiposity in C3ar1 -/-mice compared with littermate controls in the absence of significant changes in lipid profiles or weight (8,9), and has also been shown to be a key mediator of insulin resistance, as evidenced by increased insulin sensitivity in C3ar1 -/-mice (14), making it attractive to test its role in atherosclerosis; and (c) a C3ar1 -/-mouse model was readily available. In the current study, C3ar1 was identified as a causal gene for aortic lesion size in females, but not in males.…”
Section: Figurementioning
confidence: 99%
“…C3a is a powerful proinflammatory agent that recruits immune cells to sites of infection (chemotaxis) and induces immune cells to secrete bactericidal agents (via degranulation) as well as inflammatory cytokines 13,14 . Overexpression of C3a/C3aR or sustained activation of its receptor can lead to inflammatory diseases, including allergies 10 , asthma 15 , arthritis 16 , sepsis 17 , lupus 18 , diabetes 19 , psoriasis 20 , nephropathy 21 , ischaemia-reperfusion injury 22 , obesity, and metabolic and cardiovascular dysfunction 23 . C3a also reportedly has antimicrobial 24 and antifungal 25 activities.…”
mentioning
confidence: 99%